Modelling of Phosphorus and Boron Doping Concentration on SOI Wafer Based Diffusion Process - Anak Agung Ngurah Gde Sapteka; Anak Agung Ngurah Made Narottama; Kadek Amerta Yasa (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
High concentration of Boron and Phosphorus elements are required in diffusion process during the fabrication of semiconductor devices such as diode and transistor based on Silicon On Insulator (SOI) wafer. Achieving high level of these elements’ concentration is the entry point for further research in the field of electronics. For this reason, the concentration of the both elements was tested by flowing Boron and Phosphorus gas with flow rate of 1.5 litre per minute into the Nitrogen furnace for 5 minutes towards the surface of the SOI wafer samples at temperatures of 880, 900 and 950 degrees Celsius. This test was carried out at Michiharu Tabe Laboratory, Research Institute of Electronics, Shizuoka University, Hamamatsu, Japan. Furthermore, the resistivity measurements of samples with Boron and Phosphorus doping were carried out. The results of resistivity were then converted to obtain the concentrations of Boron and Phosphorus on the surface of SOI wafer sample. From the concentration and temperature data, it is obtained the modelling of concentration to temperature function for Boron and Phosphorus. The modelling results show that there is a linear correlation between high concentrations of Boron and Phosphorus to temperature.